Geology and Wine 13. Geographic Information System Characterization of Four Appellations in West Texas, USA - Hellman, Edward W.; Takow, Elvis A.; Tchakerian, Maria D.; Coulson, Robert N. (Geoscience Canada, 2011)
Texas produces approximately 90 000 hl of wine annually from more than 200 wineries and 1214 ha of vineyards. Eight wine grape production regions are officially recognized as American Viticultural Areas (AVAs) in Texas. Improved understanding of the growing conditions within each AVA facilitates selection of well-adapted cultivars that is critical for continued success and expansion of the wine industry. A geographic information system (GIS) was developed to enable enhanced characterization of the climatic, geologic and edaphic conditions of Texas AVAs. The GIS contains datasets describing climatic variables, geology, soils, elevation and topography, all of significance to grape production. This paper characterizes the four viticultural areas (AVAs) of west Texas: Texas High Plains AVA, Escondido Valley AVA, Texas Davis Mountains AVA, and Mesilla Valley AVA. Common features of the four AVAs are relatively high elevation, warm to very warm growing-season temperatures, mild winter temperatures, and low annual precipitation. Local differences in elevation and topography modify climatic conditions among AVAs, providing variations in growing degree-days and ripening-period mean temperatures that influence the performance of grape cultivars. The Texas High Plains and Texas Davis Mountains AVAs have the lowest growing degree-days and coolest ripening-period mean temperatures; Escondido Valley and Mesilla Valley AVAs are drier and warmer, resulting in fruit ripening earlier than in the High Plains and Davis Mountains AVAs. Variable underlying geology leads to differing soil types planted to vineyards in each AVA; predominantly loamy fine sands and fine sandy loam in Texas High Plains, silty clay loam and loam in Escondido Valley, loam and clay loam in Texas Davis Mountains, and clay loam and sandy loam in Mesilla Valley. West Texas produces red wines from Cabernet Sauvignon and Merlot cultivars, which are notable for good tannin and excellent colour; recent planting trends to warm-climate cultivars, including Tempranillo, Sangiovese, Mourvèdre, and Grenache, are producing blended wines of great promise. Similarly, a solid reputation for white wines from Chenin blanc and Chardonnay is being enhanced by increased production of Viognier, Vermentino, and other warm-climate varietal wines. Sommaire Texas produit environ 90 000 hectolitres de vin par année provenant de plus de 200 établissements vinicoles et 1214 ha de vignes. Huit régions de productions de raisins de cuve sont officiellement reconnues comme zones viticoles américaines (AVA) en Texas. Une meilleure compréhension des conditions de croissance au sein de chacune AVA facilite le choix des variétés, (cultivars) adaptées pour le succès et l’expansion continue de l’industrie viticole. Un système d’information géographique (SIG) a été développé pour permettre la caractérisation améliorée des conditions climatiques, géologiques et édaphiques de l’AVA de Texas. Le SIG contient les ensembles de données décrivant les variables climatiques, la géologie, les sols, l’altitude, et topographie d’importances pour la production viticole. Ce document caractérise les quatre Zones viticoles de l’Ouest Texas: Texas High Plains, Escondido Valley, Texas Davis Mountains, et Mesilla Valley. Les caractéristiques communes entre des quatre AVA sont relativement haute altitude, très chaudes températures de saison de croissance, les températures de l’hiver doux et faibles précipitations annuelles. Les variations locales en altitude et topographie modifient les conditions climatiques entre les zones viticoles américaines et entraînent des variations des degrés-jour de croissance (GDD) et la température moyenne de mûrissement (RPMT), ce qui exercent une influence sur rendement des cultivars de raisin. Le Texas High Plains et le Texas Davis Mountains zones viticoles ont les GDD les plus bas et une RPMT froide; le Escondido Valley et Mesilla Valley zones viticoles sont plus secs et plus chauds, ce qui entraine le mûrissement de fruit plus tôt que dans le High Plains et Davis Mountains AVAs. Variable géologie sous-jacente conduit à une variation des types de sol plantés aux vignobles dans chaque AVA ; principalement loam sableux et le loam sablo-argileux dans Texas High Plains, loam limoneux et loam dans Escondido Valley, loam et loam argileux dans Texas Davis Mountains, et loam argileux et loam sableux dans Mesilla Valley. Ouest Texas produit des vins rouges de Cabernet Sauvignon et le Merlot qui se distinguent par le tanin et une couleur excellente, les tendances récentes à la plantation de climat chaud cultivars, y compris le Tempranillo, le Sangiovese, Mourvèdre, et Grenache, produisent des vins d’assemblages de grandes promesses. De même, une solide réputation pour les vins blancs de Chenin blanc et le Chardonnay est améliorer par l’augmentation de la production de Viognier, Vermentino, et d’autres vins de climat chaud cépages.